Case Report: Treatment of Penile Intraepithelial Neoplasia in an Asian Male With Reconstructive Plastic Surgery - Huang, Kai; Lu, Shuai; Wang, Yehua; Tu, Xiangan (Frontiers in Surgery, 2021)
Intraepithelial Neoplasia is a special type of squamous cell carcinoma occurring in the skin epidermis. The incidence of Penile intraepithelial neoplasia in Asian males is rare. We report the clinical characteristics and treatment process of a case of Penile intraepithelial neoplasia in a Chinese man. We treated this patient's disease by surgical excision of the penile lesion and scrotal flap plastic surgery. After surgery, the shape of the penis was satisfactory, and there was no adverse effect on erection. The pathological results confirmed the diagnosis of penile intraepithelial neoplasia. The pathological features showed that the lesion tissue was covered with squamous epithelium and that there was severe atypical hyperplasia of the lesion epithelium, disordered arrangement of polarity, and an intact basement membrane. The removal the lesions of penile intraepithelial neoplasia through a wider surgical resection range, combined with the stretchability of a scrotal flap, can achieve a good healing effect of the surgical wound and reduce the possibility of recurrence of penile intraepithelial neoplasia.